REFORMASI BIROKRASI PELAYANAN PUBLIK YANG SEJALAN DENGAN KONSTITUSI DAN PRINSIP DEMOKRASI - Rizal Nurdin Ismail Nurdin; Isa Anshori (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2022)
The implementation of democracy in the management of public services is an important part that must be carried out by the bureaucracy. In its implementation, it must uphold democratic principles that are in line with the state constitution, namely freedom/equality, people's sovereignty, and open and responsible government. Better and more satisfying services for the community must be carried out by public service providers. The government's attitude is still inclined to only provide good services to certain people, who have the same political views and thoughts as the government. The paradigm of the management of the administration of the public service bureaucracy must be changed, which initially "regulates" the community to "serve" the community. because the public service bureaucracy is the main benchmark in assessing the performance of the central government and local governments in serving the community. Keywords: Bureaucratic Reform, Public Service, Democracy, Constitution.